Antecedents of Organizational Citizenship Behaviour among primary school teachers in Alor Setar / Luqman Mahmud ... [et al.] - Mahmud, Luqman; Mat Noor, Ahmad Nizan; Md Nor, Mohamad Niza; Nik Abdullah, Nik Azlina (Universiti Teknologi MARA, Perlis, 2024)
Discussion on organizational citizenship behavior (OCB) among teachers has gained much interest among scholars. However, a review of past literature indicates lack of study towards the antecednts of teachers’ OCB in Malaysia. The study aims to explore the often-overlooked informal relationships between teachers’ Organizational Citizenship Behaviour (OCB), the school environment, their level of competency, empowerment, and commitment to the team. It also seeks to understand the impact of specific elements of job satisfaction and organizational commitment on the overall benefit teachers bring to their communities. The focus of this research is to ascertain the real-world implications of these factors on OCB and their organizational effects among teachers in Alor Setar schools. To understand these interactions and their influence on teachers’ OCB, relevant hypotheses were formulated, tested, and further examined. As part of this research, 400 primary school teachers in Alor Setar were given a set of questionnaires. The regression analysis results indicated that factors such as the school environment, competency level, empowerment, and team commitment have a significant impact on teachers’ OCB. This study holds importance as it delves into the OCB of teachers and their contribution to the increasingly crucial education sector in Malaysia. The findings of this study can guide policymaking in the education sector, particularly in enhancing teachers’ OCB and school administrators can use these insights to foster a culture that promotes OCB, thereby improving overall school performance. In the school context, OCBs were found to play a role in student achievement and increase school effectiveness. They free up resources for more productive purposes, help coordinate organisational activities, and are more effective at environmental change.